Evaluating the summarization algorithms of Ask.com, Bing, Google and Yahoo: search snippets-result conformance. - Zeynali-Tazehkandi, Mahdi; Nowkarizi, Mohsen; Zhian-Feizabadi, Yeganeh (Performance Measurement & Metrics, 2025)
Purpose: Objective: The objective of the research was to evaluate the performance of the summarization algorithms utilized by Ask.com, Bing, Google and Yahoo. Design/methodology/approach: This study evaluated the summarization algorithms employed by search engines. In this regard, a set of 30 search terms was carefully constructed using schema ontology. These terms were subsequently employed to interrogate the selected search engines. A random selection of three results from each set of ten retrieved results was then extracted for thorough evaluation. The evaluation process involved quantifying the degree of relevance deviation between the search snippets and the corresponding full-text results. This analysis served to effectively measure the effectiveness of the search engines' summarization algorithms. Findings: The research findings indicated a substantial discrepancy between the relevance of search snippets and the corresponding full-text search results. Furthermore, the findings underscored notable differences among the summarization algorithms utilized by Ask.com, Bing, Google and Yahoo. Additionally, the study found that the abstracting quality of Ask.com, Bing, Google and Yahoo was 43.4, 57.2, 51.8 and 47.8%, respectively. Practical implications: Users are recommended to employ Bing and Google for conducting search queries. The developers of Ask.com and Yahoo are urged to refine their summarization algorithms. Originality/value: This study constitutes the first-ever attempt to assess the summarization capabilities of Ask.com, Bing, Google and Yahoo.